Growth performance of rice genotypes at the seedling stage under different salinity stresses - Ikbal, Mohammad Ferdous; Rafii, Mohd Y.; Ramlee, Shairul Izan; Yaapar, Muhammad Nazmin; Islam, Mirza Mofazzal; Shultana, Rakiba; Rana, Md Masud; Anisuzzaman, Mohammad; Haque, Md Azadul (Agricultural Research Communication Centre, 2024)
Background: Worldwide coastal rice growing areas are severely affected by salinity which has become a major constraint to rice production. Salinity is a serious soil problem in rice-growing countries, severely limiting global rice production. Methods: In this study, the seedlings of 21 rice genotypes were tested against seven different levels of salinity concentrations (0.3, 2, 4, 6, 8, 10 and 12 dSm-1) under a hydroponic system in a glasshouse condition at Field 10, Faculty of Agriculture, Universiti Putra Malaysia (UPM). Data on seedling growth and salinity injury of the tested rice genotypes were recorded. Result: The results showed that Pokkali, FL478 and Binadhan-10 were tolerant at 12 dSm-1; BRRI dhan73, BRRI dhan61, Binadhan-8, BRRI dhan67 and BRRI dhan47 were tolerant at 10 dSm-1; Putra-1 were moderately tolerant at 8 dSm-1 and MR263, MR284, MR211 and MRQ74 were tolerant at 4 dSm-1 and rest of the genotypes were salt susceptible. The lower amount of Na: K and Na: Ca were measured from rice genotypes, Pokkali and FL478 at maximum salinity levels. The promising rice genotypes that were tolerant at 12 dSm-1 would be taken into consideration for a hybridization program to develop a new salt-tolerant rice variety.